De la poésie comme traduction :Pound traducteur d’Arnaut Daniel - Francesca MANZARI (E-REA)
Among the recurrent motifs relating to poetry translation is the question of its impossibility. And yet, the history of Western poetry is closely connected to translation practice, to the extent that it would seem a small step to recognize in poetic activity an intrinsic inclination towards translation work, as if poetry and translation went hand in hand–as if to compose a poem were always already to translate-adapt a previously existing literary and linguistic form, whose vocation was to be transposed and thereby renewed. The translation of a poem is always an event, for while the translation of poetry is considered to be impossible, it is nevertheless absolutely necessary. In this article we study the links between the translation of poetry and literary creation by reading-writing one of the emblematic figures of the poet-translator, Ezra Pound.